'I'm Not Getting Anywhere with my Meditation …': Effort, Contentment and Goal-Directedness in the Process of Mind-Training. (20th June 2018) - Amaro, Ajahn
Abstract : This article draws on the teachings of the Pali Canon and the contemporary lineages that are guided by its principles. In particular, reference is made to the author's mentors in the Thai Forest Tradition. It explores the respective roles of goal-directed effort and contentment in the process of meditative training, and skilful and unskilful variations on these. Effort is needed, but can be excessive, unreflectively mindless, unaware of gradually developed results, or misdirected. Contentment can be misunderstood to imply that skilful desire has no role in practice, and lead to passivity; though it is needed to dampen down an over-energized mind, or motivation rooted in aversion or ambition, and comes from insight-based non-attachment. Right effort avoids the craving to become or to get rid of, but is associated with a skilful chanda/desire that is an aspect of the iddhi-pādas, the Bases of Spiritual Power. Mindfulness aids the balance of energy and concentration in the Five Faculties, and the energizing and calming qualities in the Seven Factors of Enlightenment. In the end, from practising Dhamma in a way that is truly in accordance with Dhamma (dhammānudhamma-paṭipatti), progress naturally flows from seeing and becoming Dhamma.